Pengaruh Rangsangan Pemasaran Terhadap Perilaku Ibu Rumah Tangga dalam Membeli Susu Bubuk untuk Konsumsi Balita di Kota Jambi - H, Afriani (Fakultas Peternakan Universitas Jambi, 2011)
The research aimed was to reveal the effect of marketing response such as product, promotion, milk brand on housewife’s behaviour in purchasing milk flour for children under five years old (balita) in Jambi City. The method used in this research was survey method which was done up to inferential stage. Sampling was done by using multi stage cluster random sampling, where as the samples were detemined by iterative method. Collected data were analysed by path analysis. The results showed that marketing response such as product and the brand of milk flour affected the housewife’s behaviour in purchasing milk flour for balita consumption. However marketing response such as promotion was not determine housewife’s behaviour. It could be concluded that product and the brand of milk flour affecting the housewife’s behaviour in purchasing milk flour for balita consumption in Jambi City.